Susceptibility of yam cultivars to minisett rot pathogens - Osai, E.O.; Ikotun, T.; Asiedu, Robert; Hahn, S.K. (1996)
The response of yam (Dioscorea) cultivars to artificial and natural infections with minisett rot pathogens was investigated. None of the 20 yam cultivars were resistant to Sclerotium rolfsii [Corticium rolfsii] or Trichoderma longibrachyatum. Cultivars TDa 84/093, 85/236, 85/257, TDr 608, 745, 81/453 and Efuru were not susceptible to Aspergillus niger. Cultivar TDa 382 was not susceptible to Penicillium oxalicum and TDa 84/093, 176, 382 and TDr 608 and 81/453 were mildly susceptible to Botryodiplodia theobromae.